2021
DOI: 10.1145/3449220
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Online Learning Landscape

Abstract: Hundreds of millions of people learn something new online every day. Simultaneously, the study of online education has blossomed within the human computer interaction community, with new systems, experiments, and observations creating and exploring previously undiscovered online learning environments. In this study we endeavor to characterize this entire landscape of online learning experiences using a national survey of 2260 US adults who are balanced to match the demographics of the U.S. We examine the onlin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…To begin with, the research findings indicate that the most commonly used online technologies among future English teachers in their time outside class are Google, YouTube, and social networks (Facebook, Messenger). These findings are consistent with the results of previous similar studies (Czerkawski 2012, Swanson & Walker 2015, Kashou 2016, Kross, Hargittai & Redmiles 2021.…”
Section: Types Of Online Technologies Future English Teachers Use And...supporting
confidence: 94%
See 1 more Smart Citation
“…To begin with, the research findings indicate that the most commonly used online technologies among future English teachers in their time outside class are Google, YouTube, and social networks (Facebook, Messenger). These findings are consistent with the results of previous similar studies (Czerkawski 2012, Swanson & Walker 2015, Kashou 2016, Kross, Hargittai & Redmiles 2021.…”
Section: Types Of Online Technologies Future English Teachers Use And...supporting
confidence: 94%
“…According to Statista (2022), the most popular website worldwide is Google, followed by YouTube. The study of Kross, Hargittai and Redmiles's (2021) among adults in the United States identified YouTube as the most popular online learning source, used both for formal and informal learning. YouTube is generally a very common resource for foreign language learning, as shown in the following subchapter.…”
Section: Informal Learning and Online Technologiesmentioning
confidence: 99%
“…From Wikipedia to WebMD to online courses and hobby communities on social media, the internet is increasingly central to how people learn (Kross et al, 2021). Going online can supplement or even replace other sources, such as print media, a formal education, and consulting with a doctor (Miller et al, 2021; V.…”
Section: Understanding the Online Learning Landscapementioning
confidence: 99%
“…Whereas earlier research into online learning investigated the internet as a monolithic resource (Miller, 2010), more recently scholars have sought to distinguish the different ways people turn to the internet to learn (Kross et al, 2021; Miller et al, 2021) and the consequences in areas like politics (Bode, 2016; Dimitrova et al, 2014) and health (Cinelli et al, 2020; Dobransky & Hargittai, 2012). In a survey of more than 2000 Americans conducted in 2019, Kross et al (2021) highlight the popularity of different online sources for learners. YouTube, informational articles, how-to guides, and Wikipedia were more popular.…”
Section: Understanding the Online Learning Landscapementioning
confidence: 99%
See 1 more Smart Citation